IDENTIFIKASI DAN ANALISIS MISKONSEPSI SISWA MENGGUNAKAN THREE-TIER MULTIPLE CHOICE DIAGNOSTIC INSTRUMENT PADA KONSEP KESETIMBANGAN KIMIA - Friesta Ade Monita; Bambang Suharto (Universitas Lambung Mangkurat, 2016)
Abstract. This study aims to find out the misconception of students in learning the concept of chemical equilibrium and its causes in terms of students and teachers. The method used is quantitative and qualitative method with research design in the form of descriptive survey study. The subject of research is determined by purposive sampling technique. Technique of collecting data by written test using Three-Tier Multiple Choice Diagnostic Instrument and non-test by conducting interview. Data analysis techniques use descriptive statistics with percentage and criticize their misconceptions. The result of the research shows that there are students' misconception of the concept of low-grade dynamic equilibrium, the concept of homogeneous equilibrium and heterogeneous medium criterion, the concept of medium-weighted equilibrium constant, the concept of quantitative relationships among components in medium-balance equilibrium reactions, the concept of moderate-weighted equilibrium, the concept of chemical equilibrium in industrial processes Medium criteria. The causes of student misconceptions originating from students themselves are preconception, associative thinking, abstract concept comprehension, student ability and wrong student reasoning. The causes of student misconceptions that come from the teaching teacher are the excessive use of verbal language and the small vowel, the teacher does not provide a profound explanation and emphasis on the concept and error of the teacher's explanation.Keywords: misconceptions, Three-tier, chemical equilibrium